Thermal properties and CT-DNA/BSA binding behavior of a binuclear Cu(II) complex with acylhydrazone containing naphthalene ring. Issue 7 (3rd April 2018) - Yu, Ming-Kun; Liu, Xiang-Rong; Ren, Jin-Wen; Liu, Jing-Jing; Yang, Zai-Wen; Zhao, Shun-Sheng
Abstract: A novel Cu(II) complex [Cu2 L2 (NO3 )2 ] with 2-hydroxy-1-naphthaldehyde-(4'hydroxy)phenylacetyl hydrazone (C19 H14 N2 O2 ·H2 O, HL) was synthesized. The structure of [Cu2 L2 (NO3 )2 ] was characterized by X-ray single-crystal diffraction and can be described as a distorted rectangular pyramid with binuclear coordination. IR, UV–vis and EPR spectra are used to discuss the structure of Cu(II) complex in different conditions. Magnetic properties were determined by EPR spectra and magnetic susceptibility studies, showing magnetic exchange interaction and weak antiferromagnetic exchange between two Cu(II) ions. The apparent activation energy ( E a ) of thermal decomposition of compounds indicated that the thermal stability of [Cu2 L2 (NO3 )2 ] is better than HL. The CT-DNA binding behavior of compounds was determined by UV–vis absorption and viscosity measurements and the results confirmed an intercalative binding mode with CT-DNA. K b obtained was 6.24(±0.12) × 10 6  M −1 and 3.09(±0.006) × 10 6  M −1 for [Cu2 L2 (NO3 )2 ] and HL, respectively, revealing that the binding ability of [Cu2 L2 (NO3 )2 ] with CT-DNA was stronger. The thermogenic curves of compounds interacting with CT-DNA were monitored by microcalorimetry, showing they were all endothermic reactions with reaction within 27–42 min; interaction enthalpies (Δ H ) of [Cu2 L2 (NO3 )2 ] and HL were 30.3 and 4.31 kJ mol −1 . Binding studies with BSA were evaluated by fluorescence spectroscopy and the same relative interactions were found comparing with the above CT-DNA experiments. Abstract :